Relationship between urban spatial form and seasonal land surface temperature under different grid scales. (February 2023) - Chen, Yang; Yang, Jun; Yu, Wenbo; Ren, Jiayi; Xiao, Xiangming; Xia, Jianhong Cecilia
Highlights: · Land surface temperature (LST) was similar in spring and autumn and was significantly lower in winter. · Urban spatial form (USF) indicators influence seasonal LST, and their correlation is significantly lower in autumn. · The three most important USF indicators for LST in spring and winter were SHDI, NL, and BMH, and their importance changed according to different scales. · By controlling urban building morphology of USF could effectively improve the urban thermal environment. Abstract: The urban heat island (UHI) effect is intensifying with increasing urbanization. As an important representation of the UHI effect and the urban thermal environment, it is critical to investigate the importance of evaluating urban spatial form (USF) indicators on land surface temperature (LST) to alleviate urban thermal environment problems. Therefore, in this study, we evaluated the importance of USF indicators from three perspectives: landscape pattern, building morphology, and social development, on LST at 10 grid scales in the main area of Xi'an City, using the XGBoost model. The results showed that: (1) LST was similar in spring and autumn, but significantly lower in winter. The distribution of high-temperature areas in the four seasons has its own characteristics, but the low-temperature areas are mainly distributed in the water bodies and parks in the north and south of the middle of the study area, which are less affected by the seasons. (2) Mean architecture height (MAH) is a seasonal stable factor with a cooling effect. The relationship between patch density (PD), landscape shape index (LSI), Shannon's diversity index (SHDI), contagion index (CONTAG), people density (POD), floor area ratio (FAR) and LST varies with seasons. The correlation between building density (BD) and LST is complex. (3) The degree of influence of the USF indicators on seasonal LST could be ranked in the following order: building morphology > landscape pattern > social development. (4) The appropriate size to study the relationship between USF and seasonal LST is 60 m. The highest contribution of USF to LST is building morphology, three indicators affect 43%–55% of LST. The findings of this study provide useful information for urban land-use planning and building layout, to mitigate the UHI effect.